Directory of product exhibitors (1965 AIA Convention) [front cover] - American Institute of Architects::::::::: (1965)
A pamphlet containing the Directory of Product Exhibitors for the 1965 AIA Convention. The convention was called 'Cities of the New World: XI Pan American Congress of Architects' held in Washington, D.C., June 13-18, 1965.